La Méditerranée, l’Océan et l’oikouménè dans l’œuvre de Posidonius et à travers le personnage de Pompée - Donata Villani (Pallas, 2009)
In the first century before our era, the Roman sway over the Mediterranean becomes established fact and Rome’s horizons are pushed back as far as the Ocean. Through two personages who marked that period, we try to characterise the vision of the Inner Sea and more generally of the circumambient world. The study bears on two works by the philosopher Posidonius of Apamea, his Histories and On the Ocean here set in relation with the geography of the actions of Pompey the Roman general. The two men knew each other and their links with the Mediterranean are obvious. Yet both of them are also clearly interested in the world of the margins, thus revealing a strong concern of the period. This contribution aims at characterising and understanding the vision of the Mediterranean, the oikouménè and the Ocean which transpires in the philosopher’s work and the Roman general’s actions.